2021
DOI: 10.1111/acv.12679
|View full text |Cite
|
Sign up to set email alerts
|

Definition of no‐fishing zones and fishing effort limits to reduce franciscana bycatch to sustainable levels in southern Brazil

Abstract: Franciscana dolphin Pontoporia blainvillei bycatch has been high for near six decades in western South Atlantic, with large regional variation. In 2012, the Brazilian Government‐regulated gillnet fisheries in south and southeast Brazil by reducing fishing effort and establishing no‐fishing zones. However, there is evidence that the magnitude of franciscana bycatch remains high and unsustainable. The aims of this study were to identify hotspot areas of franciscana bycatch associated with two main gillnet fisher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 41 publications
(46 reference statements)
0
21
0
Order By: Relevance
“…Evidence, however, indicates that the level of franciscana's fishing-related mortality in Brazil remains high, in the order of several hundreds to a few thousands, which is not different from the numbers observed in years that preceded the regulations (e.g., Prado et al, 2013Prado et al, , 2016Cremer et al, 2018a). Moreover, a recent case study showed that even with full compliance, the current fishing regulations cannot reduce franciscana bycatch to sustainable levels in southern Brazil (Prado et al, 2021). Therefore, these regulations are proved insufficient to reduce fishing-related mortality to sustainable levels due to either or both lack of enforcement and, hence, compliance, and insufficient reduction in fishing effort.…”
Section: Conservation Perspectivesmentioning
confidence: 99%
See 3 more Smart Citations
“…Evidence, however, indicates that the level of franciscana's fishing-related mortality in Brazil remains high, in the order of several hundreds to a few thousands, which is not different from the numbers observed in years that preceded the regulations (e.g., Prado et al, 2013Prado et al, , 2016Cremer et al, 2018a). Moreover, a recent case study showed that even with full compliance, the current fishing regulations cannot reduce franciscana bycatch to sustainable levels in southern Brazil (Prado et al, 2021). Therefore, these regulations are proved insufficient to reduce fishing-related mortality to sustainable levels due to either or both lack of enforcement and, hence, compliance, and insufficient reduction in fishing effort.…”
Section: Conservation Perspectivesmentioning
confidence: 99%
“…Meanwhile, an immediate and significant bycatch reduction, as a result of a drastic decrease of the total fishing effort, and habitat restoration is, perhaps, the only short-term options for reducing the risk of franciscana's collapse (e.g., Prado et al, 2021). These authors identified two bycatch hotspots areas in Rio Grande do Sul state coast (part of FMA III), south of Brazil, and recommended that they should be designated as no-fishing zones for gillnets.…”
Section: Conservation Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…The species is classified as ‘Vulnerable’ in the IUCN Red List of Threatened Species throughout its range (Zerbini et al ., 2017), principally as a consequence of incidental mortality in fisheries. Within the study area (Franciscana Management Area III), along the Rio Grande do Sul (RS) state coast – southern Brazil, this species has been experiencing unsustainable rates of bycatch in gillnets for at least four decades (Moreno et al ., 1997; Ott et al ., 2002; Secchi et al ., 2003; Secchi & Fletcher, 2004; Prado et al ., 2013, 2016, 2021). At a regional level, franciscana dolphins are listed as ‘Critically Endangered’ in the study region (Rio Grande do Sul State, Decree No.…”
Section: Introductionmentioning
confidence: 99%